2004
DOI: 10.2139/ssrn.556080
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Default Risk Premia from Default Swap Rates and EDFs

Abstract: the BIS held a workshop on "The pricing of credit risk". This event brought together central bankers, academics and market practitioners to exchange views on this issue (see the conference programme in this document). This paper was presented at the workshop. The views expressed are those of the author(s) and not those of the BIS. v BIS workshop on "The pricing of credit risk"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
260
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(284 citation statements)
references
References 34 publications
23
260
1
Order By: Relevance
“…While remaining model-specific, their conclusions could provide useful guidance for our research. Hence, through the estimation of default risk premia from US corporate bonds, Berndt et al (2005) find that the expected default frequencies from the Moody's KMV model explain a large proportion of the cross-sectional variation in CDS spreads. However, substantial variation is noted for a given default probability.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 97%
See 2 more Smart Citations
“…While remaining model-specific, their conclusions could provide useful guidance for our research. Hence, through the estimation of default risk premia from US corporate bonds, Berndt et al (2005) find that the expected default frequencies from the Moody's KMV model explain a large proportion of the cross-sectional variation in CDS spreads. However, substantial variation is noted for a given default probability.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 97%
“…Gilchrist et al (2011) for instance demonstrated the importance of considering the business cycle perspective in explaining the determinants of credit spreads. Similarly, Berndt et al (2005) suggest that CDS spreads are likely not attributed to credit risk alone and Annaert et al (2013) notably conclude that liquidity and global economic variables are important to explain CDS variations. More recently, Keiler and Eder (2013) investigate the degree of systemic risk and the importance of potential spill-over effects in the banking system by analyzing the determinants of CDS spreads using spatial econometric approach.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Driessen (2002) and Berndt, Douglas, Duffie, Ferguson, and Schranz (2008) provide evidence that, on average, ⇧ rt ⇡ 1.9. In other words, for every unit of actual default risk taken, the seller of protection must be compensated as if she is taking roughly double that amount of default risk.…”
Section: C5 Does Seller J Just Specialize?mentioning
confidence: 99%
“…To make Equation (19) empirically operational I need to have estimates of P rt and LGD Q rt . Like in Berndt, Douglas, Duffie, Ferguson, and Schranz (2008), I proxy for P rt using Moody's 5-year annualized EDF. 75 Analogously, I obtain separate estimates of LGD Q rt from Markit and Moody's.…”
Section: C5 Does Seller J Just Specialize?mentioning
confidence: 99%